Extension of the ζ‐method for calculating deflections of two‐way slabs based on linear elastic finite element analysis. (9th February 2021) - Tošić, Nikola; Pecić, Nenad; Poliotti, Mauro; Marí, Antonio; Torres, Lluis; Dragaš, Jelena
Abstract: Deflections are among the most complex aspects of reinforced concrete behavior. Furthermore, deflection control is increasingly a governing criterion in design, especially in the case of two‐way members such as flat slabs or edge‐supported slabs. However, simple and theoretically sound and adequately verified methods for calculating deflections of two‐way reinforced concrete members have been lacking. Therefore, in this study, a novel method is proposed for deflection control of two‐way slabs. The method is an extension of the ζ ‐method (as defined by Eurocode 2 and the fib Model Code 2010) of interpolating deflections between the uncracked and fully cracked state. As a basis, the method uses elastic deflections that are obtained through linear elastic analyses in finite element software. The elastic deflection is then adequately transformed based on the properties of a representative section, to account for cracking, shrinkage and creep according to a modified version of the ζ ‐method. Finally, the method is validated against available experimental results from literature, obtaining satisfactory precision and accuracy. The method proposed in this study aims at providing an easy‐to‐use tool for designers carrying out deflection control of two‐way reinforced concrete slabs.